Political Rights of Persons with Disabilities: Analysing the Legal Framework of Bangladesh - Akther, Farzana; Ahmed Siddiky, Chowdhury Ishrak (Dhaka University Law Journal, 2026)
The politicization of the rights of persons with disability (PWD) is crucial for developing an inclusive state model in Bangladesh. Empowering PWD in the political landscape has great implications for the overall development narratives of the State. The representative political approach does require the inclusion of PWD in the power hierarchy. Thus, this article aims to scrutinize the status of political rights of PWD in Bangladesh for understanding the scope of relevant improvements. Additionally, it analyses the existing electoral laws aligned with international and national mandates for including PWD in the political process. It argues that non-inclusivity in the political process poses a significant threat to the social and economic realities of PWD in Bangladesh. By addressing the silence and contradictions in the legal regime, the article further formulates some pragmatic suggestions for policymakers to rethink the political rights of PWD for bolstering sustainable democratic practice in national life. Dhaka University Law Journal, 2025, 36(2), 161-185